Effect of premedication on dose requirement, cardiovascular effects and recovery quality of alfaxalone total intravenous anaesthesia in dogs. (July 2019) - Dehuisser, Virginie; Bosmans, Tim; Kitshoff, Adriaan; Duchateau, Luc; de Rooster, Hilde; Polis, Ingeborgh
Abstract: Objective: To investigate alfaxalone total intravenous anaesthesia (TIVA) following premedication with methadone combined with acepromazine (ACP) or dexmedetomidine in bitches undergoing ovariohysterectomy. Study design: Prospective, blinded, randomized, experimental study. Animals: A group of 12 female Beagles. Methods: Dogs were premedicated intravenously with methadone (0.2 mg kg –1 ) combined with ACP (20 μg kg –1, group AM) or dexmedetomidine (5 μg kg –1, group DM). Anaesthesia was induced with alfaxalone (2 mg kg –1 ). Anaesthetic maintenance was obtained with an alfaxalone variable rate infusion (VRI) started at 0.15 mg kg –1 minute –1 and adjusted every 5 minutes based on clinical assessment. Mechanical ventilation was initiated when necessary to maintain normocapnia. Anaesthetic monitoring included electrocardiogram, heart rate (HR), invasive diastolic (DAP), systolic (SAP) and mean arterial blood pressure, arterial haemoglobin oxygen saturation, respiratory variables and oesophageal temperature. Data were recorded every 5 minutes. A mixed model statistical approach was used to compare cardiovascular variables within and between groups (α = 0.05). A Wilcoxon rank-sum test was used to compare body temperature, VRI alfaxalone rate, administered rescue analgesia, sedation, induction, intubation, recovery scores and recovery times between treatments. Results: Overall HR, SAP and DAP differed between groups ( p  = 0.001, 0.016, 0.019, respectively). The mean VRI dose rate of alfaxalone differed between groups DM [0.13 (0.11–0.14) mg kg –1 minute –1 ] and AM [0.18 (0.13–0.19) mg kg –1 minute –1 ; p  = 0.030]. Rescue analgesia was administered more in group AM ( p  = 0.019). No significant difference in recovery times and scores was observed between protocols. Conclusions and clinical relevance: Alfaxalone TIVA following dexmedetomidine/methadone premedication produced a more stable plane of anaesthesia to perform ovariohysterectomy than ACP/methadone. A dose reduction of alfaxalone of 27.7% was obtained in group DM compared with group AM. Recovery quality and recovery times were comparable between both groups.